THE EFFECT OF TOTAL QUALITY MANAGEMENT ON ORGANIZATIONAL PERFORMANCE WITH ORGANIZATIONAL INNOVATION CAPABILITY AS A MEDIATING VARIABLE IN CONSTRUCTION SERVICE COMPANIES IN EAST JAVA - Nadia Rizki Amalia; Liliana Dewi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
The construction sector in East Java, which contributes 9.92% to Indonesia’s GDP, faces persistent challenges such as financial losses, project delays, and a shortage of skilled labor. Despite the sector’s strategic role, previous studies have produced inconsistent findings regarding the effect of Total Quality Management (TQM) on Organizational Performance (OP). To address this gap, this research examines the direct relationship between TQM and OP and investigates the mediating role of Organizational Innovation Capability (OIC). This study adopts a quantitative-explanatory design with data collected from 104 respondents representing construction service companies in East Java. The analysis was conducted using the SEM-PLS method with SmartPLS3 software. The findings reveal that TQM positively influences OP, while TQM also enhances OIC, which in turn contributes to OP. Furthermore, OIC is confirmed to partially mediate the relationship between TQM and OP, highlighting its importance in strengthening organizational outcomes. These results provide empirical evidence that improving innovation capability is essential for maximizing the benefits of TQM in the construction sector. Future studies are encouraged to examine other potential mediators and apply advanced testing methods to further enrich the understanding of organizational performance determinants.